Translation and psychometric validation of the Korean version of the academic nurse self-efficacy scale for Korean bachelor-level nursing students - Lee Eunkyung; Park Jin-Hwa (Sciendo, 2024)
This study aimed to translate the Academic Nurse Self-Efficacy scale (ANSE), assess its appropriateness for use in Korean nursing students, and evaluate the Korean Version of the Academic Nurse Self-Efficacy scale's (K-ANSE) validity and reliability.